PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KECERDASAN EMOSIONAL DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU (STUDI DI SMA NEGERI PATI KOTA DI KABUPATEN PATI) - Anik Hastiyaningsih, 12.5202.0184; Susilowati, Yeye (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to examine the influence of emotional intelligence and profesional competence of the teachers performance of Public Senior High School with moderation organizational culture. The specific objective of this study is to examine the role of organizational culture moderate the influence of emotional intelligence and profesional competence of the teachers performance. The usefulness of this study is to clarify and extend previous study on the role of organizational culture moderate the influence of organizational commitment and pedagogical competence of the teachers performance. This study used a population of high school teachers in Pati district, Pati regency were 147 teachers. Sampling techniques in this study is non-probability sampling with purposive sampling method. The analysis technique used is the regression model of quasi moderation. Based on the results of the study, the writer can summarize as follows: the emotional inteligence does not infuent the performance of teachers, the profesional competence influences on teacher performance, the organizational culture influences the performance of teachers, the organizational culture does not moderate the influence of emotional intelligence to teacherâs performance, the organizational culture strengthen the influence of profesional competence on teacherâs performance. Keywords: emotional intelligence, profesionalÂ competence, organizational culture and teacherâs performance